Edukasi Digital Marketing Sebagai Upaya Peningkatan Pemasaran Terhadap Produk UMKM Di Desa Mojopilang - Mokhammad Ridha; Feliza Dwi A. P; Firdausi Achmad; Nurfatiqa Cahya R.S; Khalimatussa’diah; Angel Fortuna S. P; Muhammad Jihannudin R.J; Nurul Latifa; Firda Markhumatus. S; Ikhlasul Amin; Michael Adibuana; Moch Rian. A; Nuzul Alfiah; Santo Cahyo. N; Siti Nurhasanah; Sobit Dianto; Liza Natalia; Siti Aminah; Mohamad Ilham. A; Kristian Purba. K; Yustyan Ellen. F; Rachel Aura. K; Sherlly Ines. W (Universitas Kristen Indonesia Toraja, 2024)
Increasingly sophisticated technological developments can be used for business development. The most obvious impact is being able to increase sales, because digital marketing is a marketing medium that has a huge influence. The general aim of this research is to educate about the impact of digital marketing on sales volume for MSMEs in Mojopilang village. Therefore, we, students of the Real Work Lecture (KKN) at Mayjen Sungkono University, Mojokerto, are providing education to youth youth organizations in Mojopilang village about implementing digital marketing through the Shopee platform and other social media as a tool for marketing bamboo crafts in Mojopilang village. Because basically many of the human resources in Mojopilang village are old, so only the younger generation are able to implement digital marketing like this. From the research results, it is known that digital marketing still needs to be educated and taught to youth organizations to make it easier for business people to market bamboo craft products.